Biological aspects of slipper lobster (Thenus orientalis) on West Coast of Sabah, Malaysia - CHUI-FEN TEOH; ANNITA SEOK-KIAN YONG; YUDI NURUL IHSAN; NUR SYAFWANAH BINTI SAHARI; ALVIN ALVICIUS; IHSAN HANI BINTI RADZI; AUDREY DANING TUZAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Teoh C-F, Yong AS-K, Ihsan YN, Sahari NSB, Alvicius A, Radzi IHB, Tuzan AD. 2025. Biological aspects of slipper lobster (Thenus orientalis) on West Coast of Sabah, Malaysia. Biodiversitas 26: 1443-1452. Thenus orientalis, a highly sought-after Scyllaridae species, is a promising aquaculture candidate. The acquisition of reliable fishery statistics is critical to reducing overfishing risks and understanding its biological aspects, ensuring long-term viability and sustainable practices. This study analyzed the biological characteristics of sex composition, monthly sex ratio, and size frequency distribution of 922 T. orientalis (473 males and 449 females; 47.24-99.02 mm Carapace Length; CL) collected at bimonthly intervals of 10 months from April 2019 to January 2020 from the West Coast of Sabah, Malaysia and the reproductive biology of ovarian maturation stages, Gonadosomatic Index (GSI) and size at first maturity of 179 females (46.24-82.66 mm CL), has practical implications for aquaculture. The overall sex ratio was found to be 1:0.95 (?²: 0.54, P=0.46), with the highest abundance of males sampled between November and December. Thenus orientalis is distributed with an average size of approximately 64.14 mm CL, with males dominating smaller size classes (<65 mm CL) and females dominating the larger size classes. The ovarian development of T. orientalis was observed to progress through five stages: immature, early maturing, late maturing, mature, and spent, correlating with changes in the GSI ranging from 0.1256 (immature) to 2.8942 (mature). The peak of GSI coincided with lobster maturity and was accompanied by conspicuous color changes from transparent immature to dark orange mature ovaries. The monthly distribution of the different maturity stages of ovaries and ovigerous females indicated the spawning season of T. orientalis is definitely between October and May, with a major peak occurring in January and a minor peak in May. Female T. orientalis was found to reach Sexual Maturity (SMy-50) at 51.9 cm CL. This understanding of the reproductive biology of T. orientalis has practical implications for sustainable aquaculture, enhancing breeding programs and hatchery productivity and contributing to ecological studies by evaluating population resilience and environmental impact on reproduction.